2021
DOI: 10.24843/ijlfs.2021.v11.i01.p03
|View full text |Cite
|
Sign up to set email alerts
|

Regression Analysis to Determine Stature From Hand Anthropometry Among Ilocano Population in Philippines for Person Identification

Abstract: Stature determination aids the person identification during forensic investigation. The human hand research is the current topic of interest among forensic scientist, forensic medicine experts and anthropologists. Based on sample size analysis, the study involved consented 60 males and 60 females, age ranged from 18 to 55 years old. Stature and hand lengths measurements were made with Stadiometer and Vernier Calipers for analysis.  From each participant, ten hand length measurements, five from left and five fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The study was carried out in West Malaysia wherein Malaysian Indians are thickly populated and are descendants of those who migrated from India during the British era from the early 19 th century. The sample size was calculated and recruited 200 Malaysian Indians with 100 males and 100 females, following the earlier anthropological researchers [10][11][12][13]. The consented participants' ages ranged from 20 years to 60 years and are free from any type of hand injuries or deformities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was carried out in West Malaysia wherein Malaysian Indians are thickly populated and are descendants of those who migrated from India during the British era from the early 19 th century. The sample size was calculated and recruited 200 Malaysian Indians with 100 males and 100 females, following the earlier anthropological researchers [10][11][12][13]. The consented participants' ages ranged from 20 years to 60 years and are free from any type of hand injuries or deformities.…”
Section: Methodsmentioning
confidence: 99%
“…For human identification, important parameters used are stature, gender, age and race, also known as the "Big Four" and stature is considered the most important in the "Big Four" for the development of biological profiles [6]. Researchers have shown that stature can be estimated from the hand [7], handprint [8], foot [9], 2D footprint [10], 3D footprint [11], dynamic footprint [12], fingerprint [13], and bones [14][15][16]. The present study aimed to develop regression formulae to determine stature from handprint anthropometry among Malaysian Indians.…”
Section: Introductionmentioning
confidence: 99%
“…The participants' stature measurements were organized in a tabular format, displaying the mean values and standard deviations (SD) to illustrate variation between sexes. The standard error of estimate (SEE) served as a measure to assess the accuracy of predictions, which was achieved when the values were between 2 and 6 cm (Moorthy et al 2019).…”
Section: Methodsmentioning
confidence: 99%